Same end by different means: Google, Amazon, Microsoft and Meta's strategies to organize their frontier aI innovation systems - Cecilia Rikap (City, University of London, City Political Economy Research Centre (CITYPERC), 2023)
I combine quantitative methodologies and in-depth interviews to analyse United States Big Tech different strategies to organize and profit from their AI corporate innovation systems (CIS). I propose 1) "frenemies" for Microsoft, because even Chinese organizations and direct competitors integrate its CIS. 2) "University" for Google, whose AI strategy included leaving DeepMind autonomous to explore more fundamental AI but appropriation mechanisms are not translating into a clear business advantage. 3) "Secrecy" for Amazon, given its large concern with secrecty and profiting from AI. 4) And "application-centred" for Facebook; its AI CIS is the narrowest, mostly attached to its platforms.
Keywords: 330; Big Tech; Artificial Intelligence; technological innovation systems; corporateinnovation systems; Digital Capitalism